2020
DOI: 10.1016/j.ejmp.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The influence of respiratory motion on dose distribution in accelerated partial breast irradiation using volumetric modulated arc therapy

Abstract: Accelerated partial breast irradiation (APBI) is alternative treatment option for patients with early stage breast cancer. The interplay effect on volumetric modulated arc therapy APBI (VMAT-APBI) has not been clarified. This study aimed to evaluate the feasibility of VMAT-APBI for patients with small breasts and investigate the amplitude of respiratory motion during VMAT-APBI delivery that significantly affects dose distribution. Methods: The VMAT-APBI plans were generated with 28.5 Gy in five fractions. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Yamauchi et al investigated the amplitude of the respiratory motion during VMAT-APBI delivery, which signi cantly affects dose distribution, and recommended considering respiratory motion management (e.g., breath-hold and shallow breathing) if the amplitude is >5 mm [10]. We believe that treatment during free breathing is reasonable and the feasibility of nongated IGRT during a single fraction was veri ed.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Yamauchi et al investigated the amplitude of the respiratory motion during VMAT-APBI delivery, which signi cantly affects dose distribution, and recommended considering respiratory motion management (e.g., breath-hold and shallow breathing) if the amplitude is >5 mm [10]. We believe that treatment during free breathing is reasonable and the feasibility of nongated IGRT during a single fraction was veri ed.…”
Section: Discussionmentioning
confidence: 90%
“…Yue et al reported that the phase difference uncertainty in the respiratory cycle between images is considered insigni cant due to the fact that the respiration induced target movement is relatively small [21]. In previous studies examining respiratory motion of the breast, the mean ± SD of the respiratory motion in the LR, SI, and AP directions were 0.5 ± 0.6 mm, 1.7 ± 1.3 mm, and 2.3 ± 1.8 mm in the study by Yamauchi et al [10] and 1.0 ± 0.6 mm, 1.3 ± 0.5 mm, and 2.6 ± 1.4 mm in the study by Kinoshita et al [25].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…8 Hence, in DIBH, dose can be delivered as per plan to critical structures as well as PTV compared to FB. 23 This phenomenon should be weighed high when we are delivering high dose per fraction of few fractions (1-5 fractions).…”
Section: Discussionmentioning
confidence: 99%